(Breaking) Intergenerational Transmission of Mental Health - Aline Bütikofer; Rita Ginja; Krzysztof Karbownik; Fanny Landaud (Institute of Labor Economics (IZA), 2023)
We estimate health associations across generations and dynasties using information on healthcare visits from administrative data for the entire Norwegian population. A parental mental health diagnosis is associated with a 9.3 percentage point (40%) higher probability of a mental health diagnosis of their adolescent child. Intensive margin physical and mental health associations are similar, and dynastic estimates account for about 40% of the intergenerational persistence. We also show that a policy targeting additional health resources for the young children of adults diagnosed with mental health conditions reduced the parent-child mental health association by about 40%.
Keywords: I14; I18; J12; J62; 330; mental health; intergenerational persistence; dynastic effects; public policy